Looming Effects on Attentional Modulation of Prepulse Inhibition Paradigm - Wu, Zhemeng; Bao, Xiaohan; Liu, Lei; Li, Liang (Frontiers in Psychology, 2021)
In a hazardous environment, it is fundamentally important to successfully evaluate the motion of sounds. Previous studies demonstrated “auditory looming bias” in both macaques and humans, as looming sounds that increased in intensity were processed preferentially by the brain. Here in rats, we used a prepulse inhibition (PPI) of the acoustic startle response paradigm to investigate whether auditory looming sound with intrinsic warning value could draw animals’ attention and dampen the startle reflex caused by the startling noise. We showed looming sound with duration of 120 ms enhanced PPI compared with receding sound with the same duration; however, when both sound types were at shorter duration/higher change rate (i.e. 30 ms) or longer duration/lower rate (i.e. more than 160 ms), there was no PPI difference. This indicates looming sounds induced PPI enhancement was duration dependent. We further showed isolation rearing impaired animals’ abilities to differentiate looming and receding prepulse stimuli, although it didn’t abolish their discrimination between looming and stationary prepulse stimuli. This suggests isolation rearing compromised their assessment of potential threats from approaching objects and receding objects.